The Influence of Behavioral Finance on Investment Decision-Making: Understanding the Role of Overconfidence and Risk Perception in Stok Market Trends (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study examines the influence of behavioral finance factors, specifically overconfidence and risk perception, on investment decision-making and stock market trends in the Indonesian market. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze survey data from individual investors, the findings reveal that overconfidence positively impacts both investment decisions and market trends, while risk perception significantly shapes cautious investment behaviors and collective market sentiment. Additionally, the interaction between overconfidence and risk perception influences investment decisions, highlighting the interplay between cognitive biases and subjective risk assessments. The study provides theoretical contributions by integrating these constructs into a unified model and offers practical implications for investor education, risk management, and market regulation. The results underscore the importance of addressing behavioral biases to enhance investment strategies and promote market stability.